Antecedents of Patient Satisfaction and Its Impact on Intention to Recommend at XYZ Aesthetic Clinic - Handoyo Alphanto, Alvin; Wuisan, Dewi Sri Surya; Yuliana, Merryl Esther (Universitas Muhammadiyah Yogyakarta, 2025)
The aesthetic clinic industry in Indonesia has experienced rapid growth, with the number of clinics increasing by approximately 6% annually, driven by high demand among Indonesian women to maintain their skin health. In the face of growing competition, aesthetic clinics must integrate traditional service approaches with various effective factors, taking into account both provider and patient perspectives. The patient-centered principle, which prioritizes the needs and preferences of the patient, becomes a key focus in improving service quality. This study aims to analyze the factors that influence patient satisfaction and the intention to recommend services at aesthetic clinics. Through a PLS-SEM model approach, the research findings revealed that physician behavior, price, social media engagement, and service quality exerted a significant positive effect on patient satisfaction. Meanwhile, the clinic’s image did not have a significant impact on patient satisfaction. Patient satisfaction was found to have a significant positive effect on the intention to recommend the clinic to others. This research provides valuable insights for aesthetic clinic management in developing more effective service strategies that focus on patient satisfaction to maintain competitiveness in this increasingly competitive industry.